Formation Constants of Hydrazine Derivative with Co, Ni, Zn, Cd and its Antimicrobial Evaluation: Formation Constants and Antimicrobial Evaluation - Gulzar, Asad; Ali, Qamar; Ahmad, Naveed; Raees, Muhammad; Fatima, Rida (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Formation constants of hydrazine derivative with Co, Ni, Zn and Cd were determined by Job’s methods of continuous variation using UV/Visible spectrophotometer at 350nm, 392nm and 420nm. The highest values of formation constants were found as 8.771 for Co, Ni and Zn; whereas the lowest formation constant was found as 6.678 for Cd. The evaluation of antimicrobial activities revealed intermediate results against Escherichia coli, Staphylococcus aureus and Candida albicans